Comportamento reprodutivo caprino e ovino com o uso do efeito macho interespécie - Vitaliano, Aline Bezerra (2011)
This study was carried out to observe the sexual behavior of individuals (male sheep, goats and female goats) during their interaction effect of male and interspecies-sexual partner for the development of a behavioral ethogram. For that, the frequency of behavioral activities during the course of the male effect was observed, both by the ram (interspecies) and by the goat regarding the female goat in the morning and afternoon. Data were subjected to analysis of variance at 5% probability. 21 Nulliparous crossbred Anglo-Nubian x Saanen goats were used, with mean age of 10.3 ± 0.6 months and mean weight of 44.5 ± 4.5 Kg, a native breeding white Morada Nova woolless sheep, with 04 years of age and 53.0 Kg, and a Saanen goat breeder, with 7 years of age and body weight of 65.0 Kg. The air temperature (TA) and relative humidity (RH) were evaluated with a digital thermohygrometer INCONTERM ®, and TA and RH data were used to calculate the temperature and humidity index (THI), calculated for each month during the study period. The variable CV (sniffed the vulva) was the most expressed during the entire assessment for the two species in question, which shows the inspection of the male in the female in estrus detection. In the morning the sheep was higher than the goat (P <0.05) in the inspection of the female in estrus, 525 vs. 210. But in the afternoon the goat was higher, 134 vs. 197. The male sheep when compared with the male goat, regardless of the turn, showed better sexual performance with a greater number of behavioral activities to induce and synchronize estrus in dairy goats. Acceptance by the female goat of the male sheep demonstrates that there is sexual interaction between different species, and that pheromones are perceived by receptors, thus triggering the estrus and related sexual behaviors.